The joint effect of weight-adjusted waist index and physical activity on all-cause mortality in Chinese elderly patients with multimorbidity: A study based on the CLHLS from 2011 to 2018 - Bingbing Fan; Kexin Ren; Lang Li (PLoS ONE, 2025)
Background The relationship between physical activity changes, weight-adjusted waist circumference index (WWI), and mortality risk among older Chinese adults with multimorbidity remains unclear. This study aimed to examine whether changes in physical activity and WWI modify the mortality risk by analyzing data from the Chinese Longitudinal Healthy Longevity Survey (CLHLS). Method Our study was based on the 2011 ~ 2018 wave of the CLHLS, involving a study of 2,626 older adults with multimorbidity. Cox proportional hazards models were employed to estimate hazard ratios (HRs) and 95% confidence intervals (95% CIs) and a stratified analysis was conducted to assess the combined impact of WWI and physical exercise on all-cause mortality in patients with multimorbidity. Result Patients with multimorbidity who engaged in regular physical activity exhibited a 41% reduction in all-cause mortality compared to those who had never been physically active (HR:0.59, 95% CI:0.49, 0.70). All-cause mortality was increased by 13% in patients with high WWI and multimorbidity compared to those with low WWI (HR:1.13, 95% CI:1.01, 1.27). Furthermore, WWI-stratified analyses revealed that varying physical activity profiles had a more pronounced protective or detrimental impact on all-cause mortality among multimorbidity patients in the high WWI group compared to the low WWI group. Conclusion This study demonstrates that both initiating and maintaining physical activity significantly reduce mortality risk in multimorbid older adults, even those with higher WWI. Our findings support integrating structured exercise interventions and routine WWI monitoring into clinical care to improve survival outcomes in this population.